Exploring Intermediate Students' Awareness and Interest in Occupational Therapy as a Career Choice - Jan, Khushboo; Qadir, Nazish A; Ehtisham, Mariya; Syed, Khawla Ilyas; Razzaq, Mukhlis; Burki, Subhan Ur Rehman (Journal of Health and Rehabilitation Research, 2024)
Background: Occupational Therapy (OT) plays a crucial role in the healthcare system, aiding individuals of all ages to regain or maintain their independence and improve their quality of life. Despite its importance, there is a noted gap in awareness and interest among students, particularly in regions like Peshawar, Pakistan, where the understanding of OT's scope and career potential appears limited. Objective: This study aimed to assess the level of knowledge, awareness, and interest among high school students (pre-medical) in Peshawar regarding Occupational Therapy as a career choice, and to compare these insights with existing perceptions of OT as a field. Methods: A cross-sectional survey was conducted among 160 high school students preparing for medical entrance examinations in Peshawar, using a validated questionnaire that encompassed demographic details, knowledge, awareness, and interest in OT. The questionnaire was structured into three parts, featuring both open and closed-ended questions. Data analysis was performed using SPSS version 25.0, focusing on descriptive statistics to summarize demographics, knowledge levels, and interest in OT. Results: The majority of participants (65%) exhibited an average knowledge about OT, with 29.7% having poor knowledge and only 5.3% showing good knowledge. Interest in OT as a career was low, with only 17.5% of the participants expressing a desire to pursue OT in the future. Misconceptions about OT were prevalent, with 65% of respondents mistakenly identifying OT as a branch of psychiatry and a substantial number underestimating the scope of OT practice. Conclusion: The study revealed a moderate understanding and a generally low interest among pre-medical students in Peshawar towards OT as a career choice. There is a critical need for enhanced educational efforts and awareness campaigns to clarify the role and scope of OT and to foster a greater appreciation for the profession among potential future healthcare professionals.